1990
DOI: 10.1002/pola.1990.080280814
|View full text |Cite
|
Sign up to set email alerts
|

Controlled “living” anionic polymerization of glycidyl methacrylate

Abstract: SynopsisThe living anionic polymerization of glycidyl methacrylate (GMA) in THF at low temperature initiated with diphenyl hexyl lithium, 9-anthracenyl methyl lithium, and a-methylstyryl lithium leads to well characterized homo-and block copolymers, with predictable and narrow molecular weight distributions and with all the oxirane groups intact. Broadening of the molecular weight distributions above a certain and very critical supported the idea that the living polymerization at low temperature might proceed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…It is worth noting that Leemans et al have reported on the broadening of the molecular weight distribution of PGMA when the chain length is increased, which has been accounted for by the decreasing solubility of longer PGMA chains in THF at low temperature. 14 In this work, the inconvenience of PGMA insolubility is alleviated by attachment of the PGMA blocks to long PBD chains perfectly soluble in THF at low temperature.…”
Section: Resultsmentioning
confidence: 98%
“…It is worth noting that Leemans et al have reported on the broadening of the molecular weight distribution of PGMA when the chain length is increased, which has been accounted for by the decreasing solubility of longer PGMA chains in THF at low temperature. 14 In this work, the inconvenience of PGMA insolubility is alleviated by attachment of the PGMA blocks to long PBD chains perfectly soluble in THF at low temperature.…”
Section: Resultsmentioning
confidence: 98%
“…7,8 In the present paper, the THF solution of living poly(MMA-co-GMA) was prepared in a similar way (see Experimental). The initial monomer concentrations were fixed at Table I, M n ϭ 2990, M w /M n ϭ 1.07) and the molecular weight distributions are narrow in all cases (M w /M n ϭ 1.07-1.13; see Table I).…”
Section: Preparation Of the Thf Solution Of The Living Poly(mma-co-gma)mentioning
confidence: 99%
“…As shown in Scheme 1, the THF solution of the living random copolymer of MMA and glycidyl methacrylate (GMA) was prepared by the anionic copolymerization of the two monomers according to a reported method. 7,8 Because the epoxy groups of the GMA units in the copolymer (1 in Scheme 1) remained unreacted, an in situ coupling reaction was carried out by introducing a benzene solution of the anionic living poly(St) or polyisoprene (poly(Is)) into the above living copolymer solution. In this manner, a pure graft copolymer (2 in Scheme 1) consisting of a poly(MMA-co-GMA) backbone and poly(St) or poly(Is) side chains was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Since many living anionic polymers of substituted methacrylate monomers with functional groups have been synthesized at the present time, [23][24][25][26][27][28][29][30][31][32][33][34][35] various functional segments can be intentionally incorporated into dendron-like hyperbranched polymers. In this section, we have synthesized a series of dendronlike hyperbranched block copolymers consisting of PMMA and PRfMA segments in order to design and synthesize effective surface-functionalized materials.…”
Section: Synthesis Of Dendron-like Hyperbranched Block Copolymers Conmentioning
confidence: 99%